2021
DOI: 10.1017/s0007114521004487
|View full text |Cite
|
Sign up to set email alerts
|

Peanut meal extract fermented with Bacillus natto attenuates physiological and behavioural deficits in a d-galactose-induced ageing rat model

Abstract: Our previous studies have shown that the nutritional properties of peanut meal after fermentation are markedly improved. In this study, in order to facilitate the further utilization of peanut meal, we investigated the effects of its fermentation extract by Bacillus natto (FE) on cognitive ability, antioxidant activity of brain, and protein expression of hippocampus of aging rats induced by D-galactose. Seventy-two female SD rats aged 4-5 months were randomly divided into six groups: normal control group (N), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…After fermentation by B. natto , the contents and utilization rates of bioactive components such as peptides and polysaccharides in peanut meal were significantly increased, and some beneficial microorganisms and bioactive substances in the fermentation could reach the intestinal tract and could improve the intestinal microecological balance, thereby preventing the occurrence of diseases 14 . Moreover, peanut meal extract fermented by B. natto has been found to promote growth and development, improve learning and memory ability in mice in our previous study 15 …”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…After fermentation by B. natto , the contents and utilization rates of bioactive components such as peptides and polysaccharides in peanut meal were significantly increased, and some beneficial microorganisms and bioactive substances in the fermentation could reach the intestinal tract and could improve the intestinal microecological balance, thereby preventing the occurrence of diseases 14 . Moreover, peanut meal extract fermented by B. natto has been found to promote growth and development, improve learning and memory ability in mice in our previous study 15 …”
Section: Introductionmentioning
confidence: 90%
“…14 Moreover, peanut meal extract fermented by B. natto has been found to promote growth and development, improve learning and memory ability in mice in our previous study. 15 At present, there are increasing studies on fermentation of mixed strains, and in mixed systems, there are some microorganisms that can mutualistically symbiosis with each other, promote each other, and improve the rate and yield of reactions. 16 It has been shown that mixed fermented horse milk with lactic acid bacteria, yeasts, and Monascus is able to regulate blood lipid levels in hyperlipidemic mice.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus natto has strong acid and heat resistance and a strong ability to inhibit pathogenic bacteria, which help it to maintain intestinal balance and promote intestinal health. 10 As a probiotic, B. natto can secrete various extracellular enzymes, including protease, cellulase, and amylase, 11 which break down large molecular substances to transform them into digestible small molecular compounds such as amino acids and polypeptides. 12 Metabolites such as nattokinase, and vitamin K 2 , of B. natto could exert important thrombolysis and type 2 diabetes (T2D) risk-reduction effects.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus natto , a subspecies of Bacillus subtilis , was named because of its first isolation from the traditional fermented food, natto. Bacillus natto has strong acid and heat resistance and a strong ability to inhibit pathogenic bacteria, which help it to maintain intestinal balance and promote intestinal health 10 . As a probiotic, B .…”
Section: Introductionmentioning
confidence: 99%